Childhood psychological problems in school settings in rural Southern Africa. - Melissa A Cortina; Mina Fazel; Tintswalo Mercy Hlungwani; Kathleen Kahn; Stephen Tollman; Mario Cortina-Borja; Alan Stein (PLoS ONE)
Background Many children can be exposed to multiple adversities in low and middle-income countries (LMICs) placing them at potential risk of psychological problems. However, there is a paucity of research using large representative cohorts examining the psychological adjustment of children in school settings in these countries. Children's psychological adjustment has been shown to affect educational progress which is critical for their future. This study, based in a rural, socio-economically disadvantaged area of South Africa, aimed to examine the prevalence of children's psychological problems as well as possible risk and protective factors. Methods Rates of psychological problems in 10-12 year olds were examined using teacher- and child-report questionnaires. Data on children from 10 rural primary schools, selected by stratified random sampling, were linked to individual and household data from the Agincourt health and socio-demographic surveillance system collected from households over 15 years. Results A total of 1,025 children were assessed. Teachers identified high levels of behavioural and emotional problems (41%). Children reported lower, but substantial rates of anxiety/depression (14%), and significant post-traumatic stress symptoms (24%); almost a quarter felt unsafe in school. Risk factors included being a second-generation former refugee and being from a large household. Protective factors highlight the importance of maternal factors, such as being more educated and in a stable partnership. Conclusion The high levels of psychological problems identified by teachers are a serious public health concern, as they are likely to impact negatively on children's education, particularly given the large class sizes and limited resources in rural LMIC settings. Despite the high levels of risk, a proportion of children were managing well and research to understand resilience could inform interventions.